2005
DOI: 10.2113/jeeg10.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Data Uncertainty in Surface Wave Inversion

Abstract: Although in recent years surface wave methods have undergone significant development that has greatly enhanced their capabilities, little effort has been spent to determine the uncertainty associated with surface wave measurements. The objective of this study is to determine how the uncertainty of the experimental data is mapped into the uncertainty of the shear wave velocity profile via the inversion algorithm. The methodology developed in this study for estimating the uncertainty of the shear wave velocity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 12 publications
4
51
0
Order By: Relevance
“…(a) Comparison between the best-fitting theoretical dispersion curves (in grayscale, according to misfit values) and the inverted dispersion curve (red dots). The uncertainty intervals (red bars) correspond to the assumption of a 5% phase velocity standard deviation at all frequencies consistent with the hypothesis of a Gaussian distribution for the population of phase velocity at each frequency (Lai et al, 2006;Safani et al, 2006;Pasquet, 2014). (b) Feasible V S profiles (in grayscale, according to misfit value) and selected model for inclusion in the initial model (for the dispersion curves comprised between 35 < x < 75 m).…”
Section: Rayleigh-wave Attenuation Curvessupporting
confidence: 66%
See 1 more Smart Citation
“…(a) Comparison between the best-fitting theoretical dispersion curves (in grayscale, according to misfit values) and the inverted dispersion curve (red dots). The uncertainty intervals (red bars) correspond to the assumption of a 5% phase velocity standard deviation at all frequencies consistent with the hypothesis of a Gaussian distribution for the population of phase velocity at each frequency (Lai et al, 2006;Safani et al, 2006;Pasquet, 2014). (b) Feasible V S profiles (in grayscale, according to misfit value) and selected model for inclusion in the initial model (for the dispersion curves comprised between 35 < x < 75 m).…”
Section: Rayleigh-wave Attenuation Curvessupporting
confidence: 66%
“…The temporal variability of the acquired data sets (dispersion and attenuation curves) and the inverted V S models were investigated to quantitatively define a seasonal trend that can be correlated with the correspond to the assumption of a 5% phase velocity standard deviation at all frequencies, consistent with the hypothesis of a Gaussian distribution for the population of phase velocity at each frequency (Lai et al, 2006;Safani et al, 2006;Pasquet, 2014). The illustrated dispersion curves are spatially referenced to x ¼ 25, 50, 75, and 100 m.…”
Section: Discussionmentioning
confidence: 99%
“…The Jacobian can also be used to propagate uncertainties on the dispersion curve to uncertainties on the shear wave velocity profile (Lai et al 2005).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…They claim that the Comment on "Shear wave profiles from surface wave inversion: the impact of uncertainty on seismic site response analysis" By Socco et al 4 uncertainty bounds are based on the results reported in Lai et al (2005), but the relation adopted by the Authors [±∆VR = ±(0.05VR + 100/f)] is not reported by Lai et al (2005) and it leads to results which are not consistent with experimental data of Lai et al (2005). It is also to be observed that the expression proposed by the Authors, can lead to uncertainties higher than 100% and negative velocity values for soft soils at low frequencies (e.g.…”
mentioning
confidence: 99%